The effects of Hibiscus sabdariffa Linn. on the levels of FGF21 and AMPK in the Heart of Diabetic Mice - Amelia, Rossa; Goenarjo, Roman Ardian; Kartinah, Neng Tine (The International Journal of Medical Science and Health Research, 2024)
Background : Diabetes Mellitus (DM) is a metabolic disorder characterized by pancreatic cell dysfunction and insulin resistance. Fibroblast Growth Factor 21 (FGF21) is thought to have a cardioprotective role. Through FGF21 signaling, AMP-activated protein kinase (AMPK) activity reduces apoptosis, inflammation, hypertrophy, and fibrosis in the heart. Hibiscus sabdariffa Linn. (HSL) contains flavonoids that have hypoglycemic effects and are anti-inflammatory and antioxidant-active. This study aims to assess the effect of HSL on FGF21 and AMPK levels in the heart of diabetic mice models. Methods : An experimental study using Deutschland Denken Yoken (DDY) mice aged eight weeks were divided into four groups: Control, DM Control, HSL 200, and HSL 400. In the DM control, HSL 200, and HSL 400 groups, diabetes was induced by giving a High Fat Diet(HFD) and STZ 40mg/kgbb. The HSL 200 group was given HSL 200mg/kgBB supplementation for three weeks, and the HSL 400 group was given HSL 400 mg/kgBB supplementation for three weeks. FGF21 and AMPK levels were measured using the enzyme-linked immunosorbent assay (ELISA) method. Results : There was no significant difference between FGF21 and AMPK levels between the control and DM control groups. FGF21 and AMPK levels in the HSL 400 group were higher than in the control, DM control, and HSL 200 groups. Conclusions : These findings suggest that HSL supplementation at specific doses can potentially increase the activation of FGF 21 and AMPK signaling in the heart of diabetic mice models.